Mutual learning for reducing tax gaps in V4 countries and Ukraine. Peer country paper: Poland - Iakov Frizis; Krzysztof Głowacki; Katarzyna Mirecka (Center for Social and Economic Research (CASE), 2017)
The paper summarizes knowledge on tax gaps in Poland with respect to PIT, CIT, VAT, and excise. An introduction to the Polish tax system is given, trends in tax collect ability and estimates of the tax gaps are discussed, and methods of combating tax evasion and avoidance are reviewed. The paper has been written as part of the project "Mutual Learning for Reducing Tax Gaps in V4 Countries and Ukraine" co-financed by the Visegrad Fund in the years 2016‒2017.
Keywords: H26; H60; 330; tax gap; tax evasion; tax avoidance; tax administration; compliance costs; CIT; PIT; VAT; excise; Visegrad; V4; Poland